Investigation of disinfectant’s effectiveness as to contaminating microflora in sugar production - Gusyatinska, Natalia; Nechypor, Tatiana (My University, 2018)
The article presents the results of the studies of the effectiveness of disinfection means, based on chlorinated guanidines, tetradic ammonium salts, dichlorisocyanuric acid, peracetic acid and hydrogen peroxide as to the contaminating microflora of sugar beets. There was investigated the influence of disinfectants on bacteria Bacillus subtilis, Leuconostoс mesenteroides, mycelia fungi Aspergillus niger, Penicillium chrysogenum and yeast Sacharomyses сerevisiae. It was experimentally established, that the studied means has the high effectiveness as to most microorganisms that cause saccharose losses in the process of its extracting from beet chip and result in worsening a technological quality of semi-products of beet-sugar. There was established the high effectiveness of modern disinfection means as to inhibiting slime-forming bacteria of Leuconostoc generis. There was proved a possibility of their use at different technological stages of beet-sugar production for preventing the development of mucous bacteriosis. It was determined that means consumption depends on a type and extent of microbiological contamination of raw materials, semi-products, technological waters at sugar production. There were established concentrations of the studied means as to inhibiting the development of main contaminants of the microflora of raw materials and semi-products in sugar production. There is offered to use the studied means in industrial beet-sugar production that would favor the decrease of microbial contamination of semi-products and the increase of a sugar output from a raw material unit. В статті наведено результати досліджень ефективності дії сучасних дезін-фекційних засобів на основі хлорованих гуанідинів, четвертинних амонієвих солей, дихлорізоціанурової кислоти, надоцтової кислоти та перекису водню щодо контамінуючої мікрофлори цукрових буряків. Досліджено вплив дезінфектантів на бактерії Bacillus subtilis, Leuconostoс mesenteroides, міцеліальні гриби Aspergillus niger, Penicillium chrysogenum та дріжджі Sacharomyses сerevisiae. Експериментально встановлено, що досліджувані засоби мають високу ефективність стосовно більшості мікроорганізмів, які спричиняють втрати сахарози в процесі її екстрагування з бурякової стружки та призводять до погіршення технологічної якості напівпродуктів бурякоцукрового виробництва. Встановлено високу ефективність сучасних дезінфікуючих засобів щодо пригнічення розвитку слизоутворювальних бактерій роду Leuconostoc. Підтверджено можливість їх використання на різних технологічних стадіях бурякоцукрового виробництва для попередження розвитку слизистого бактеріозу. Визначено, що витрати засобу залежать від характеру та ступеня мікробіологічного забруднення сировини, напівпродуктів, технологічних вод у виробництві цукру. Встановлено концентрації досліджуваних засобів щодо пригнічення розвитку основних контамінантів мікрофлори сировини та напівпродуктів у виробництві цукру. Пропонується використання досліджуваних засобів у промисловому бурякоцукровому виробництві, що сприятиме зменшенню мікробного обсіменіння напівпродуктів та сприятиме збільшенню виходу цукру з одиниці сировини.
Keywords: sugar beets; disinfectant; dextran; diffusion apparatus; mucous bacteriosis; цукрові буряки; дезінфектант; декстран; дифузійний апарат; слизистий бактеріоз; кафедра технології цукру і підготовки води